2012
DOI: 10.1590/s1517-86922012000500009
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do ΔF sobre a acomodação da corrente interferencial em sujeitos saudáveis

Abstract: Aims: To evaluate in how much time the interferential current (IFC) accommodation occurs, and how many times this accommodation happens in 10 minutes using different patterns of variations in the frequency of stimulation: ∆F null = 0; ∆F low = 30% and ∆F high = 70%. Materials and methods: crossover trial, with 15 volunteers, with mean age of 22.53 ± 0.91 years, of both genders. The patients were submitted to IFC for 10 minutes as bipolar with the electrodes longitudinally arranged on the vertebrae L1 and S1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
6
0
4
Order By: Relevance
“…However, although there are technical ways of limiting the accommodation threshold, its effectiveness is questionable. As a consequence, a periodic manual rise of the current amplitude is needed [10,11]. Therefore, studies addressing the accommodation variables regarding differences between genders are relevant in order to look for special procedures while stimulating male or female populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although there are technical ways of limiting the accommodation threshold, its effectiveness is questionable. As a consequence, a periodic manual rise of the current amplitude is needed [10,11]. Therefore, studies addressing the accommodation variables regarding differences between genders are relevant in order to look for special procedures while stimulating male or female populations.…”
Section: Discussionmentioning
confidence: 99%
“…In order to test the accommodation phenomena, all participants were positioned lying down to receive the IC applied in a tetrapolar arrangement, 4000Hz (100 Hz AMF) [10,11] for 20 minutes. The equipment used was the Neurovector Sapphire Line (Ibramed ® , Brazil), which has the IC both in the bi-or tetra-polar form; carrier frequency of 2, 4 or 8 kHz; amplitude modulated frequency and slope between 1-100 Hz, and ramp delivery slope of 1:1, 1:5:1 or 6:6 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For chronic low back pain, intensity considered as "high", however "comfortable", is able to decrease pain 2 . IC has tools looking at preventing sensitivity to current accommodation, such as Δf and slope, however they have not shown to be effective to change accommodation threshold 9,10 . Previous studies investigating such parameters have shown frequencies similar to those investigated herein.…”
Section: Discussionmentioning
confidence: 99%
“…There are still controversies about ideal modulation ranges as well as about the role of AMF 7,8 and other parameters. Among them, there is Δf (frequency amplitude) and slope (Δf slope patterns, usually with variations in 1:1, 1:5:1 or 6:6 seconds, indicated for chronic, sub-acute and acute cases, respectively) 9,10 . Accommodation is a phenomenon induced by decreased number of nervous depolarizations due to repetitive and prolonged stimulation.…”
Section: Introductionmentioning
confidence: 99%